A Review on Antiretroviral Tablets (International Journal of Scientific Research in Science and Technology, 2024)
The usage of fixed dose combination (FDC) tablets of Lamivudine, Dolutegravir and Tenofovir Disoproxil Fumarate (TDF) is increasing due to increased incidences of HIV/Hepatitis B and HIV/TB co-infections. This is likely to increase the financial crisis due to limited resources for funding procurement of ready-made products from the pharmaceuticals manufacturing leading countries. Therefore, production of local oral tablets containing Lamivudine and TDF FDC is inevitable. Lamivudine 300 mg/TDF 300 mg tablets were developed and optimized by D-optimal mixture design and produced by direct compression technique. The first-ever 2-drug regimen approved for the treatment of HIV-1 infection for treatment-naive people living with HIV (PLWH), consisting of the integrase inhibitor dolutegravir (DTG) and the nucleoside reverse transcriptase inhibitor (NRTI) lamivudine (3TC), is reviewed in this paper. The chemical composition and properties, pharmacokinetic and pharmacodynamics profile, and clinical trial data on efficacy and safety of DTG/3TC are presented. An expert opinion aims to highlight important considerations for the use of DTG/3TC in the context of existing and emerging ARV options.